Toruński Informator "Solidarności" . 09 September 1987 (Wydanie Specjalne) - Cichoń, Wiesław; Spandowski, Roman; Kaczor, Andrzej; Sienkiewicz, Radek; Borek, Piotr; Musielak, Ryszard (s.n.], 1987)
Creation and circulation: From issue no. 10=227(1989)published legally